Cultural Policy and Art Markets. The Festival de las Artes as a Project of the Costa Rican State (1989-2017) - Fernández Picado, Mario (2025)
Introduction: The Festival de las Artes has clearly established fundamental principles but has experienced significant instability in its organization. Objective: It analyzes the process of institutionalization of the Festival de las Artes from four perspectives: operations, programming, artistic trends, and budgets. Methods: It utilizes regulations, bylaws, institutional reports, newspaper articles, and journals to construct discussions, identify key actors, and illustrate trends within the festival. Results: The aim is to identify the actors involved in shaping the project and the changes imposed, as well as to delineate the trends in programming and artistic expression, alongside budgetary considerations. Conclusions: The Festival de las Artes, as a cultural initiative of the State, represents an institution subject to transformation influenced by the interests and decisions of specific historical figures; furthermore, this initiative has fostered an art market, as the Costa Rican State established a cultural policy that supported its development.